Accelerating ant colony optimization by using local search - Tabassum, Nabila; Haque, Maruful (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.